Certain Foaming Characteristics of Crude Saponins of Seeds of Balanites aegyptiaca del. (Journal of Environmental Bioremediation and Toxicology, 2023)
This study evaluated the foaming characteristics of crude saponins extracted from the seeds of Balanites aegyptiaca and compared them with commercially available detergents, Tween 80 and Triton-X-100, across concentrations ranging from 0.2% to 1.0%. Foam heights were measured at 0, 1, and 5 minutes, and total foaming times (T, hours) were recorded. The results showed that foam height increased with concentration for all substances, indicating improved foaming capacity. Crude saponins demonstrated a highest foam height of 3.35 ± 0.13 cm at a 1.0% concentration with a foaming time of 4.68 ± 0.32 hours, suggesting moderate foam stability. In comparison, Tween 80 and Triton-X-100 exhibited superior foaming properties, with maximum foam heights of 8.60 ± 0.24 cm and 12.35 ± 0.09 cm, and foaming times of 20.70 ± 0.49 hours and 41.27 ± 0.33 hours, respectively. Statistical analysis revealed no significant differences in foam heights among the three solutions (p > 0.05). However, foam stability, indicated by foam retention percentage (R5%), was highest for Triton-X (90.8%), followed by Tween 80 (85.3%) and crude saponins (54.5%). These findings suggest that while crude saponins have lower foam power and stability compared to synthetic detergents, they still demonstrate significant foaming properties, making them a potential eco-friendly alternative in applications where moderate foam stability is adequate. The study highlights the importance of concentration in determining foam performance, particularly for natural saponin-based foaming agents.
Keywords: Saponins; Balanites aegyptiaca del.; Foam power; Foam stability; Foam Height